Sero-Surveillance of Infectious Laryngotracheitis in Layer Birds in Bangladesh - Jahan, Mohammad Sorwar; Khan, Mohammad Ferdousur Rahman; Nazir, KHM Nazmul Hussain; Amin, Md Mansurul; Rahman, Md Bahanur (Microbes and Health, 2013)
Infectious Laryngotracheitis (ILT) is an economically important respiratory disease primarily of chicken caused by Infectious Laryngotracheitis Virus (ILTV) belonging to the family Herpesviridae. After infecting its host, the virus induces immune response; antibodies are produced, which can be easily detected by several immunological or serological methods like Enzyme-Linked Immunosorbent Assay (ELISA). In the present study, the research work was conducted to reveal the prevalence of antibodies (IgG) against ILTV in layer birds in Bangladesh during the period of July 2010 to April 2011. A total of 324 blood samples were collected randomly from 30 layer farms located in 15 different districts in the country, and subsequently sera were prepared. Aiming to detect the antibody against ILTV, the sera samples were subjected to indirect ELISA using a commercial ILTV Antibody Test kit. Out of 324 sera samples examined, a total of 299 (92.28%) were positive. The results indicate that layers in the selected poultry farms were exposed to ILTV in Bangladesh and confirms the prevalence of this virus in a wider scale since the first report of its existence in 2010. DOI: http://dx.doi.org/10.3329/mh.v1i2.14086 Microbes and Health, 2012 1(2): 38-40